STUDI FENOLOGI DAN PENGARUH POSISI BUAH SERTA UKURAN BENIH TERHADAP VIABILITAS BENIH GMELINA (Gmelina arborea Roxb) - Jan Barlian; Hediani Yeni; , Masano (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
The objective of this research was to study the development of the flower and fruit, to enable determining physiological maturity (PM) and the effect of fruit position and seed size on seed viability of Gmelina. Gmelina seed reaches physiological maturity at the age 32 days after anthesis to have maximum potential viability, vigor and seed dry weight. Fruit position has significant effect on germination potential. Seed size do not affect parameter observed, and so is the interaction between seed position and seed size. Fruit from the middle part of the tree's stand has the highest germination potential and those from the top has the lowest. Seed having small (size 15-20 mm) has better viability compared with the big ones (> 20 mm) and seed from the fruit of the top and below which size 15-20 mm and > 20 mm.